Low order robust ν-gap metric H∞ loop shaping controller synthesis based on particle swarm optimization - Konghuayrob, Poom; Kaitwanidvilai, Somyot (My University, 2017)
The strong demand of the data storage capacity has been increasing significantly. According to the heat-assisted magnetic recording (HAMR) technology, the demand trend of hard disk drive (HDD) is predicted that the areal density will be achieved 10 Tbit/in2 before the year 2020. High areal density results in a narrow track pitch which is quite sensitive to the external disturbance including the measured noise. This point is the benchmark problem of the high precision controller design for controlling the HDD servo mechanism. Moreover, the systematic uncertainties have to be taken into consideration in controller design procedure as well. The alternative robust ν-gap metric related to H∞ loop shaping is proposed in this paper to stabilize a voice coil motor in HDD under the uncertainty condition. The potential particle swarm optimization (PSO) is adopted to minimize the gap between the plant with H∞ controller and the plant with specified 3 controller orders. Instead of using the conventional H∞ controller with high order with a complicated structure, this paper applies the proposed lower controller order based on ν-gap which is more appropriate implement in the actual application. The performance and robustness of both controllers are compared in the simulation studies. The results confirm the similar characteristics of both controllers in terms of performance tracking and disturbance rejection. Furthermore, the system stability index called stability margin with 0.472 and system perturbations testing condition also emphasizes the robustness and effectiveness of the proposed controller.
Keywords: H∞ loop shaping; Hard disk drive; Robust controller; Voice coil motor; ν-gap